Pengaruh Kemudahan Penggunaan dan Kemanfaatan yang Dirasakan terhadap Minat Muzakki Membayar Zakat Secara Digital (Pendekatan Technology Acceptance Model) - Muhammad Ilham; Haikal Al Amin (JURNAL RUMPUN MANAJEMEN DAN EKONOMI, 2026)
This research aims to find out the influence of leadership and organizational culture on teacher performance at Darussalam Ciputat High School in South Tangerang, both partially and simultaneously. The type of research uses the associative quantitative method. The sampling technique uses a saturated sample of 52 respondents. Data analysis techniques use: data instrument test, classical assumption test, simple linear regression, multiple linear regression, correlation coefficient, determination coefficient. Hypothesis test using t test and F test. The results of the analysis show: The influence of leadership has a partial positive effect on teacher performance with a simple linear regression equation Y = 4,343 + 0,991 X1. The correlation coefficient value of 0.86 means that it has a very strong relationship level and a determination coefficient of 0.753 means that teacher performance is influenced by leadership influence of 75.3%. This is proven by the t test obtained the calculated t value > t table (12,335 > t table 1,675) and reinforced by a significant value < 0.05 (0.000 < 0.05). Organizational culture partially has a positive effect on teacher performance, shown by the simple linear regression equation Y = 4,629 + 0,926 X2. The correlation coefficient value of 0.928 means that it has a very strong relationship and the determination coefficient of 0.861 means that performance is influenced by competence of 86.1%. This is proven by the t test obtained the calculated t value > t table (17,602 > t table 1,675) and reinforced by the significance value < 0.05 (0.000 < 0.05). The results of the research on the influence of leadership and organizational culture simultaneously on teacher performance at Darussalam Ciputat High School in South Tangerang were shown by the multiple linear regression equation Y = 3,046 + 0,254 X1 +0,730 X2, a correlation coefficient value of 0.934, which means that it has a very strong relationship level and a determination coefficient of 0.872, which means that performance is influenced by work experience and competence of 87.2%. This is proven by the results of the hypothesis test F test obtained the calculated F value > F table (167,041 > 3,187) and reinforced with a significance value < 0,05 (0,000 < 0,05). Thus it is proven that Ho was rejected and Ha was accepted.